2021
DOI: 10.3390/s21206748
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Assessment of Honey Using Fast Fourier Transform

Abstract: Ultrasound inspection permits the characteristics of some foodstuffs to be determined easily and cheaply. This experimental study included the determination of various ultrasound parameters provided by the fast Fourier transform (FFT) which had not previously been considered in testing the physical properties of different varieties of honey. These parameters are practically independent of the criteria adopted for their calculation, unlike other ultrasound variables such as pulse velocity or attenuation whose d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
2
2
0
Order By: Relevance
“…Finally, the frequency of the bending loads was extracted by fast Fourier transform (FFT), showing a frequency domain representation of the amplitude for the continuous signal obtained from the time domain, allowing one to visualize its frequency range. 50 FFT plots, shown in Figure 4f, identify the frequencies with the maximum amplitude of each SLJ subjected to bending, which agrees well with the experimental bending interval (∼0.17 Hz). All SLJs show the same frequency of 0.175 Hz, except for 5 wt % MWCNT/PP-GF/PP SLJs due to their noisy electrical resistance signal.…”
Section: ■ Results and Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Finally, the frequency of the bending loads was extracted by fast Fourier transform (FFT), showing a frequency domain representation of the amplitude for the continuous signal obtained from the time domain, allowing one to visualize its frequency range. 50 FFT plots, shown in Figure 4f, identify the frequencies with the maximum amplitude of each SLJ subjected to bending, which agrees well with the experimental bending interval (∼0.17 Hz). All SLJs show the same frequency of 0.175 Hz, except for 5 wt % MWCNT/PP-GF/PP SLJs due to their noisy electrical resistance signal.…”
Section: ■ Results and Discussionsupporting
confidence: 83%
“…These distinct, consistent, and reversible changes in electrical resistance response show the potential of nanocomposite films for damage monitoring of TPC joints due to their high sensitivity and stability. Finally, the frequency of the bending loads was extracted by fast Fourier transform (FFT), showing a frequency domain representation of the amplitude for the continuous signal obtained from the time domain, allowing one to visualize its frequency range . FFT plots, shown in Figure f, identify the frequencies with the maximum amplitude of each SLJ subjected to bending, which agrees well with the experimental bending interval (∼0.17 Hz).…”
Section: Resultssupporting
confidence: 81%
“…Recently, non-destructive methods, including X-Ray, optical, spectroscopic, and ultrasonic techniques, have been applied to characterize various kinds of food products [5][6][7]. However, only a few studies deal with the characterization of viscous fluids such as honey [8,9]. Nevertheless, ultrasound is one of the widely used non-destructive inspection tools in the rheological characterization and monitoring of various kinds of liquid, including vegetable oil [10], organic liquids [11,12], biological fluids [13] and colloidal suspension [14].…”
Section: Introductionmentioning
confidence: 99%
“…However, only a few studies reported its application for quality monitoring of highly viscous food products such as honey. One such recent study reports the shift in the received nominal frequency as the ultrasound wave propagates through the honey sample [8]. It relates the FFT with the texture properties of honey.…”
Section: Introductionmentioning
confidence: 99%